1979
DOI: 10.1044/jshd.4403.321
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Language Samples Elicited at Home and in the Clinic

Abstract: One of the most common methods of obtaining diagnostic information about a child's language production is to collect and analyze a spontaneous language sample. Usually, this sample is collected in a clinical setting by a speech-language pathologist. Because children's language production seems very sensitive to situational variables, there is some question about the representativeness of language samples obtained in clinical settings. This study compared language samples obtained in the home by the mothers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
5
25
0
Order By: Relevance
“…This would suggest multiple assessments with some chldren in order to achieve an accurate. In a study which examined DSS scores of samples obtained in the home and in the clinic settings, Kramer et al (1979) used different stimulus materials to obtain the samples. To obtain the clinic samples, a conversation task was used presenting toys and books where necessary.…”
Section: Effects Of Stimulus Materials On Dss Scoresmentioning
confidence: 99%
“…This would suggest multiple assessments with some chldren in order to achieve an accurate. In a study which examined DSS scores of samples obtained in the home and in the clinic settings, Kramer et al (1979) used different stimulus materials to obtain the samples. To obtain the clinic samples, a conversation task was used presenting toys and books where necessary.…”
Section: Effects Of Stimulus Materials On Dss Scoresmentioning
confidence: 99%
“…By analyzing a child's spontaneous, tape-recorded speech sample, the speech-language clinician is able to estimate the extent to which grammatical rules have been sufficiently generalized for use in the child's verbal performance. In recent years, the DSS has been used as a comparative measure in speech and language studies and used extensively as an analytical tool in determining expressive language delay (Carrow, 1974b;Longhurst and File, 1977;Kramer, James, and Saxman, 1979).…”
Section: Ro Ert:h:englis~mentioning
confidence: 99%
“…Johnson (1974) stated that the familiarity of a child's social context influences his/her language production. Scott, Taylor, and White (1975), Olswang andCarpenter (1978), andKramer et al (1979) compared the quality of language collected in the home by mothers with that collected in the clinic by speech-language pathologists. Scott et al (1975) reported that sentences with greater complexity and length were produced in the home environment; whereas, the other two studies showed no significant difference in the lexical, syntactical, and semantical aspects of the language between the home and clinical environments, but the investigators reported that mothers elicited greater amounts of language per set time periods.…”
Section: !!! Language Samplesmentioning
confidence: 99%
“…The investigators concluded that all three of the stimulus conditions will produce adequate language samples; however, the use of conversation or the children's personal toys may be more efficient than the use of clinic toys. Kramer et al (1979) compared the MLU and DSS scores for language samples elicited in the home by mothers and in the clinic by speechlanguage pathologists for ten children from Syracuse, New York.…”
Section: Uses Of the Developmental Sentence Scoring Normative Datamentioning
confidence: 99%
See 1 more Smart Citation